Knowledge and perception of first year Malay female undergraduate students at public university in Malaysia towards human papillomavirus vaccination - Hamid, Muhamad Hadri; Jusoh, Siti Nurhamidah Fadilah; Ang, Janice Su Chern; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2014)
Background: In Malaysia cervical cancer is the third most common cancer for women after breast and colorectal cancer. Malaysia has implemented a national Human Papillomavirus (HPV) vaccination programme targeting to Form 1 secondary school girls since 2010.Thus, it is important to assess the knowledge and perception among young girls to evaluate the effectiveness of the programme. The objectives of the study are to assess the level of knowledge and perception of female first year students at public university in Malaysia towards HPV vaccination. Methodology: One public university was randomly selected from 15 public universities, and 354 first year Malay undergraduate female students in the university were randomly selected to participate in the study. Pre-tested questionnaires developed by researchers were used as instrument of the study. Results: Total of 346 out of 349 respondents participated in the study, and response rate was 99%. The study results showed that 52% of respondents obtained good level knowledge on HPV vaccination with the median score of 66, and inter-quartile range of 5. Perception toward HPV vaccination showed 53.3% of the respondent’s attained poor perception with median score of 50, and inter-quartile range of 9. The study showed that there are association between level of knowledge and level of perception of respondent’s with family history of HPV infection (P<0.05), and level of perception also showed association with urban or rural background of respondent’s (P<0.05). Other factors such as cost of HPV vaccination and family history of cervical cancer show no association with level of knowledge and perception of respondents toward HPV vaccination. Conclusion: Knowledge of first year Malay female students at public university studied regarding HPV vaccination is good, but their perception is poor. Family history of HPV infection was associated with knowledge and perception of respondents toward HPV vaccination, and rural and urban background of respondents only shows association with perception.